1991
DOI: 10.1002/qua.560400307
|View full text |Cite
|
Sign up to set email alerts
|

Normalized irreducible tensorial matrix expansions applied to an effective sp‐type Hamiltonian for the PES of water

Abstract: Any matrix can be expanded on a basis of su(2) normalized irreducible tensorial matrices, NITM, defined in terms of 3-j symbols or coupling coefficients of su(2). The NITM transform under rotations according to Wigner's matrices. If one dimension of an NITM is odd and the other even, the tensor has half-integer rank. A simple NITM basis consists of all NITM having the same numbers of rows and columns as the expanded matrix. A compound NITM basis consists of two or more simple bases, each spanning a correspondi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1992
1992
2003
2003

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 18 publications
(11 reference statements)
0
5
0
Order By: Relevance
“…1. When both representations are irreducible, (4.3) is a simple basis of M(ω 1 ×ω 2 ) discussed previously. , Using (3.12) for semisimple groups with coupling frequencies of zero or one, elements of the NITM are given by where φ is an appropriate phase factor, V is Griffith's V coefficient for finite groups or a 3-j symbol for SU(2), and r̂ 1 is an appropriate contragredient index.…”
Section: Gnitmmentioning
confidence: 99%
See 2 more Smart Citations
“…1. When both representations are irreducible, (4.3) is a simple basis of M(ω 1 ×ω 2 ) discussed previously. , Using (3.12) for semisimple groups with coupling frequencies of zero or one, elements of the NITM are given by where φ is an appropriate phase factor, V is Griffith's V coefficient for finite groups or a 3-j symbol for SU(2), and r̂ 1 is an appropriate contragredient index.…”
Section: Gnitmmentioning
confidence: 99%
“…A notable exception is the mixing of the |2s N 〉 and |2p zN 〉 orbitals, absent in the overlap paradigm. With this term included [ H ] N , N fits the superposition model. , …”
Section: Ammoniamentioning
confidence: 99%
See 1 more Smart Citation
“…(1.1) shown to be or-(1. 2) and, by the Wigner-Eckart theorem [6], to transform under elements of SU (2) according to the Wigner rotation matrices [7] It was further shown that the set of NITM { [~~) ] ( " ' ) , k = ljj'l,. .. , j + j ' ; 4 = -k, .. .…”
Section: Tr([ N Y ](Lj')[n$')](jj')) = 6(k K ' ) S(q Q ' )mentioning
confidence: 99%
“…2) and, by the Wigner-Eckart theorem [6], to transform under elements of SU (2) according to the Wigner rotation matrices [7] 0 1992 John Wiley & Sons, Inc.…”
Section: Introductionmentioning
confidence: 99%